Dual career through the eyes of university student-athletes in the Republic of Kosovo - Gjaka, Masar; Feka, Kaltrina; Tessitore, Antonio; Thomas, Abbey; Capranica, Laura (Frontiers in Sports and Active Living, 2024)
The successful combination of a sports career and education, known as the dual career, requires cooperation and a multi-dimensional approach. Although extensive research has been conducted on dual career programs and services in developed countries, there is limited information available on the dual-career phenomenon in developing countries. This study aimed to explore the dual career experiences of university student-athletes in the Republic of Kosovo. A 30-item online survey was distributed to student-athletes, addressing various aspects of the dual career. A total of 121 student-athletes (males: 63.6%; females: 36.4%) voluntarily participated in the survey. These student-athletes represented 13 different sports, with 102 (84.3%) participating in team and 19 (15.7%) in individual sports. Between individual and team sports no significant differences were found regarding university and sports engagement, and the time required to travel from the university to the training venue, whereas a significant difference (p = 0.019) emerged for the time needed to travel from home to the training venue. Significant differences (p<0.05) were found between university majors in terms of sports engagement. The present findings highlight a lack of familiarity with dual career programs among student-athletes (89.3%) and the need for dual-career policies at the university (16.5%), sport (9.9%), and national (13.2%) levels. Student-athletes faced various challenges, mainly related to limited leisure time (62.8%), academic overload (60.3%), frequent absence from classes (59.6%), and financial uncertainty (35.5%). Recommended improvements included increased financial support (66.1%), the availability of sports facilities at or near the university (48.8%), greater educational flexibility (26.4%), tutoring services at the university (25.6%), and sports clubs (19%) levels, as well as improved communication regarding existing initiatives and legal aspects (53.7% and 47.1%, respectively). The study also identified parents (98.3%), coaches (86%), and siblings (60.3%) as important sources of support for student-athletes at personal, sports, and university levels. In conclusion, to enhance the potential of future student-athletes in the Republic of Kosovo, relevant stakeholders in sports and higher education should collaborate closely and implement programs and services based on international best practices for dual-career support.